Augusto Pinochet U. y la memoria heroica de la dictadura cívico-militar en Chile (1973-1989) - Paulina Pavez Verdugo (Les Cahiers ALHIM)
This paper examines some symbolic dimensions of “Pinochetismo” during the Chilean post-dictatorship period by analysing the social practices and representations built around the figure of Augusto Pinochet that have made possible for some sectors of the Chilean society to build and legitimize a heroic memory of the dictatorship. This thesis aims to explore some answers to these questions from the perspectives of the New Cultural History and Steve Stern´s (2006) approach to the subject of Heroic Memory of dictatorship in Chile.